Barriers to Innovation and the Innovative Performance of Portuguese Firms - Madeira, Maria Jose (2020)
This paper aims to identify and analyze the main limiting factors of innovation performance in terms of product and process innovation. The limiting factors to innovation make the innovation process of a firm difficult, which influences its innovation performance. The goal of this essay is to develop a theoretical support based on current reference approaches, corroborated by empirical support, which allows for the identification and analysis of the factors that restrict innovation activity and innovation performance. The database is extracted from the Community Innovation Survey - CIS 2010, which was conducted under the responsibility of the Office of Planning, Strategy, Evaluation and International Relations/Ministry of Science, Technology and Higher Education (GPEARI/MCTES), in collaboration with the National Statistics Institute (INE), under the supervision of EUROSTAT. We have developed a logistic regression model that highlights the barriers to innovation and identifies the factors that limit innovation performance.The analysis suggests that several barriers to innovation influence the Innovative performance of Portuguese firms. These results may be attributed to the fact that perceived barriers stimulate the firm to overcome these difficulties, which promotes the internal propensity to innovate. The most significant barriers identified in the study are the following: high innovation costs and perceived uncertainties in both the demand and market for new goods and services. This study shows that firms that do not have either qualified personnel to carry out innovation activities or sufficient market information are less likely to innovate than firms that do not experience these difficulties.